NGO Influence in International Organizations: Information, Access and Exchange. Issue 1 (15th September 2015) - Tallberg, Jonas; Dellmuth, Lisa M.; Agné, Hans; Duit, Andreas
Abstract : While there is broad consensus that non-governmental organizations (NGOs) sometimes succeed in influencing policy making within international organizations (IOs), there is much less agreement on the factors that make NGO lobbying effective. This article makes two contributions to this debate. First, the determinants of influence among NGOs active in different IOs, issue areas and policy phases are examined. The analysis builds on original survey data of more than 400 NGOs involved in five different IOs, complemented by elite interviews with IO and state officials. Secondly, the article advances a specific argument about how the strategic exchange of information and access between NGOs and IOs increases NGO influence in IOs. This argument, derived from theories of lobbying in American and European politics, is contrasted with three alternative explanations of NGO influence, privileging material resources, transnational networks and public opinion mobilization, and the broader implications of these results for research on NGOs in global governance are explored.